A longitudinal study of psychological functioning and academic attainment at the transition to secondary school. Issue 3 (10th April 2013) - Riglin, Lucy; Frederickson, Norah; Shelton, Katherine H.; Rice, Frances
ABSTRACT: This longitudinal study of adolescents in the first year of secondary school, examined the relationship between psychological functioning at the beginning of year 7 (mean age 11.25 years) with attainment at the end of year 7 (mean age 11.78 years). Depressive symptoms, school liking and conduct problems predicted lower attainment across time having controlled for the temporal stability in psychological functioning and attainment. School concerns predicted lower attainment for boys only, and the effects of depressive symptoms on later attainment were significantly stronger for boys compared to girls. School liking – and school concerns for boys – remained significant predictors of attainment when controlling for conduct problems. The transition to secondary school may represent a window of opportunity for developing interventions aimed at improving both pupil psychological functioning and attainment. Highlights: ► Psychological functioning at the start of secondary school predicted later grades. ► Depressive symptoms, school liking and conduct problems predicted lower grades. ► School liking predicted later grades when controlling for conduct problems. ► Boys showed poorer grades following emotional problems and affect towards school. ► This period may be appropriate for targeting psychological functioning and grades.